Big Data in Tourism Destinations: A Systematic Literature Review - Widarti, Erni; Erkamim, Moh.; Wartono, Wartono (Institut Riset dan Publikasi Indonesia, 2024)
Tourism is an industrial sector that has a variety of data originating from tourists. This data can be utilized and reprocessed through the application of artificial intelligence technology such as big data and machine learning to analyze and predict tourist patterns so that it can be used in developing the tourism sector. This research aims to present a systematic literature review regarding the role of big data and machine learning in the tourism context. This research reviews 25 research papers related to big data and machine learning applied in the tourism industry. The categorization of tourism research related to big data and machine learning is based on research published from 2018 to 2023. The focus of this research is to provide an in-depth review based on journal rankings, research objectives, types of data used, and algorithms applied in the research . The results of this research are to provide a systematic literature review that can be used to help future researchers discover new research topics and present insights into future prospects regarding the use of big data and machine learning in tourism.